How do SOEs and FIEs affect POEs’ performance in emerging economies? Moderating effects of managerial ties - Tang, Qingqing (Springer Nature, 2020)
In emerging economies, informal ties are important instruments that firms use to overcome market competitiveness disadvantages. Higher proportions of state-owned enterprises (SOEs) and foreign-investment enterprises (FIEs) tend to hinder the performance of privately-owned enterprises (POE); from this foundation, this study investigates whether and how two forms of informal ties—managerial business and political ties—help POEs mitigate these negative effects. Findings from 717 listed POEs in China’s manufacturing sectors confirm that high proportions of SOEs and FIEs limit the POEs’ performance in the same industry. Business ties can mitigate the negative effect of SOEs; political ties weaken the detrimental effect of FIEs. However, business ties have limited capability to alleviate the negative effect of a high proportion of FIEs, and political ties cannot buffer the negative effect of a high proportion of SOEs. These findings thus specify ways that firms can leverage their informal ties to remedy their disadvantages in emerging economies.